Optimizing Msme-Based Financial Information Through Qris Synergy and HR Competence - Wenny A. Ginting; Shane A. Pangemanan; Siti Aisyah Nasution (YAYASAN BINA BISNIS NUSANTARA MEDAN, 2026)
This study analyzes the influence of QRIS adoption and human resource (HR) competence on the financial quality of UMKM in Manado City. Using a quantitative approach with survey data from 125 UMKM in the restaurant sector collected through a census method, multiple regression analysis was conducted. The results indicate that QRIS adoption has a positive and significant impact on financial quality, as it improves transaction management, cash flow, and the accuracy of financial reporting. This supports the Technology Acceptance Model (TAM), which emphasizes perceived usefulness and ease of use in technology adoption. HR competence also shows a positive and significant effect, consistent with the human capital theory, which highlights the importance of skilled HR in improving performance. Together, QRIS and HR competence significantly affect financial quality with an R² of 0.592. The findings suggest that combining digital adoption and HR competence is more effective than each factor alone, with implications for practice, theory, and policy in strengthening UMKM financial sustainability.